Blends of Non-caloric Sweeteners Saccharin and Cyclamate Show Reduced Off-Taste due to TAS2R Bitter Receptor Inhibition. Issue 10 (19th October 2017) - Behrens, Maik; Blank, Kristina; Meyerhof, Wolfgang
Summary: Non-caloric sweeteners are widely used for the formulation of calorie-reduced beverages for health-conscious consumers. However, disadvantages such as undesired off-tastes limit the use of non-nutritive sweeteners. Therefore, the food industry is constantly searching for novel sweeteners and frequently resorts to using blends combining non-caloric sweeteners in a single formulation. The earliest blend allowing higher sweetness levels with reduced bitter off-taste combined saccharin with cyclamate. However, the mechanism by which sweetener blends become superior to single compounds remained obscure. By functional expression of human bitter taste receptors, we found the explanation for the phenomenon observed ∼60 years ago. We demonstrate that cyclamate potently blocks the receptors responsible for saccharin's bitter off-taste. This effect occurs at concentrations where cyclamate itself does not elicit a side taste. Intriguingly, also saccharin inhibits cyclamate-activated bitter receptors. Our experiments demonstrate that heterologous assays are useful for understanding perceptual phenomena and the development of novel tastant formulations. Graphical Abstract: Highlights: TAS2Rs responsible for saccharin's bitter off-taste are blocked by cyclamate Saccharin suppresses cyclamate-activated bitter taste receptor responses Saccharin and cyclamate blends do not elicit supra-additive sweet receptor signals Abstract : The mechanism by which non-caloric sweetener blends become superior to single compounds is obscure. By functional assays, Behrens et al. found that combining the sweeteners cyclamate and saccharin led to mutual suppression of the bitter receptors activated by the single substances.